Pairing surgery with laparoscopic cholecystectomy in single sitting - Resutra, Ritvik; Mahajan, Neha; Gupta, Rajive (International Surgery Journal, 2019)
Background: With advancement in laparoscopic surgery a number of surgical procedures can be performed combined with laparoscopic cholecystectomy for treating coexisting abdominal pathologies in a single surgery. We evaluated the safety and efficacy of such surgeries when paired in a single sitting with laparoscopic cholecystectomy. Methods: A retrospective review of all patients who had undergone combined procedures with laparoscopic cholecystectomy during the period from May 2016 to July 2019 at Maxx life hospital, Bathindi, Jammu was performed, 1200 laparoscopic cholecystectomies were performed during the study period. Of these, 400 cases were combined with another procedure, out of which, 348 were combined laparoscopic procedures and 52 were open procedures combined with laparoscopic cholecystectomy. Results: All the combined surgical procedures were performed successfully. The mean operative time was 70 minutes (range 50-180 min). The longest time was for the patients who had undergone laparoscopic cholecystectomy with Laparoscopic assisted vaginal hysterectomy (180 min). The mean hospital stay was 2 days (range 1-5 days). Conclusions: As long as the basic surgical principles and indications for combined procedures are adhered to, more patients with concomitant pathologies in the abdomen can enjoy the benefits of minimal access surgery and also one-time anaesthesia without significant addition in post-operative morbidity and hospital stay.